(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Currently, technologies ICTs offer different alternatives for use in education, thus making it easier for educational subjects to be able to more efficiently manipulate data, study tools, experiments, etc. All this through artificial intelligence. (AI) which have recently had an important impact on education. According to UNESCO (2019), it seeks to give good management to AI since it is a fact that they are now part of our lives. This work seeks to analyze the impact of artificial intelligence (AI) in positive aspects and others that are not so influential, in order to know and search for the ethical means for the proper use of artificial intelligence.